A system of orthopaedic medicine - Ombregt, Ludwig (Churchill Livingstone/05Elsevier, 2013)
Since its first publication, almost two decades ago, A System of Orthopaedic Medicine has proven to be a reliable resource and guide for those clinicians working in the field of orthopaedic medicine who assess and treat the effects of musculoskeletal pain. This third edition remains focused on clinical reasoning and diagnosis, with detailed guidance on palpation of the anatomical structures and the correct performance of each therapeutic technique. Following the 'System', the clinician first completes a systematic clinical assessment of the joints involved, and then, after interpreting the results, groups the disorders and conditions into clinical syndromes. Finally, the natural history and the conservative treatment of each condition are discussed accordingly. NEW! Building on the previous edition, A System of Orthopaedic Medicine now comes with access to online resources designed to support and enhance the learning experience of each and every clinician using the book. The new edition has been streamlined for easier access and handling by transferring all the applied anatomy chapters, references, links and other selected chapters onto the online resources.